Diagnostic Performance of NLR, Type IV Collagen and Fibrosis Score in Chronic Hepatitis B - WA. Arsana; BRA. Sidharta; A. Kurniati; JB. Suparyatmo; MID. Pramudianti (Indonesian Association of Clinical Pathologist and Medical laboratory, 2022)
Hepatitis B Virus (HBV) infection cause damage to the liver parenchym and continuous injury resulting in liver fibrosis. The neutrophil-lymphocyte ratio is a non-invasive marker of inflammation. Type IV collagen is a direct marker of hepatic fibrosis indicating transformation of the extracellular matrix of the liver, and its concentration is proportional to the degree of damaged liver cells and impaired liver function. APRI score and FIB-4 index are non-invasive methods for determining the degree of liver fibrosis. This study aimed to determine the performance of the neutrophil lymphocyte ratio, type IV collagen and fibrosis score on liver fibrosis in chronic hepatitis B. The study design was analytical observational with cross-sectional approach. The subjects included 42 chronic hepatitis B patients who admitted to Internal Medicine Department of Dr. Moewardi Hospital Surakarta from September to November 2020. The subject were grouped into fibrosis 21(50%) and non fibrosis groups 21(50%) based on transient elastography. Neutrophil lymphocyte ratio, type IV collagen and fibrosis score cut off point was determined with receiver operating curve (ROC) and diagnostic test was performed with 2x2 table. The cut-off point of 1.89 from the neutrophil lymphocyte ratio obtained sensitivity 61.9% and specificity of 38.1% with an AUC value of 0.524, while type IV collagen with a cut off point of 18.32 ng/mL obtained sensitivity 80.9% and specificity of 42.6% with an AUC of 0.642, a cut off 0.25 from the APRI score obtained a sensitivity of 81% and specificity of 61.9% with an AUC of 0.857, and cut-off FIB-4 of 0.68 obtained a sensitivity of 85.7% and specificity of 71.4 with AUC of 0.827. Neutrophil lymphocyte ratio with cutoff point of 1.89 has a weak diagnostic value on liver fibrosis in chronic hepatitis B. Further study by comparing or combining with other markers are needed. Type IV collagen with a cut off of 18.32 ng/mL, APRI score with a cut off of 0.25 and a FIB-4 index with a cut off of 0.68 can be used for screening liver fibrosis in chronic hepatitis B patients